Gamification in Management: Between Choice Architecture and Humanistic Design. (April 2019) - Deterding, Sebastian
Gamification in management is currently informed by two contradicting framings or rhetorics: the rhetoric of choice architecture casts humans as rational actors and games as perfect information and incentive dispensers, giving managers fine-grained control over people's behavior. It aligns with basic tenets of neoclassical economics, scientific management, operations research/management science, and current big data-driven decision making. In contrast, the rhetoric of humanistic design casts humans as growth-oriented and games as environments optimally designed to afford positive, meaningful experiences. This view, fitting humanistic management ideas and the rise of design and customer experience, casts managers as "second order" designers. While both rhetorics highlight important aspects of games and management, the former is more likely to be adopted and absorbed into business as usual, whereas the latter holds more uncertainty, but also transformative potential.